2013
DOI: 10.1021/cb400569k
|View full text |Cite
|
Sign up to set email alerts
|

A Bidirectional System for the Dynamic Small Molecule Control of Intracellular Fusion Proteins

Abstract: Small molecule control of intracellular protein levels allows temporal and dose-dependent regulation of protein function. Recently, we developed a method to degrade proteins fused to a mutant dehalogenase (HaloTag2) using small molecule hydrophobic tags (HyTs). Here, we introduce a complementary method to stabilize the same HaloTag2 fusion proteins, resulting in a unified system allowing bidirectional control of cellular protein levels in a temporal and dose-dependent manner. From a small molecule screen, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 26 publications
3
32
0
1
Order By: Relevance
“…Additionally, the best structure-based inhibitor showed strong stabilization effects, raising the melting temperature of DmbA by 6°C. Similar effects have been observed with HaloTag stabilizers (42) and with DatA enzyme during crystallization experiments (44). Increased thermostability of the enzyme, while retaining its activity, represents an interesting strategy for extension of its half-life during industrial biocatalysis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Additionally, the best structure-based inhibitor showed strong stabilization effects, raising the melting temperature of DmbA by 6°C. Similar effects have been observed with HaloTag stabilizers (42) and with DatA enzyme during crystallization experiments (44). Increased thermostability of the enzyme, while retaining its activity, represents an interesting strategy for extension of its half-life during industrial biocatalysis.…”
Section: Discussionsupporting
confidence: 69%
“…S4 in the supplemental material). A similar binding motif has been observed in the crystal structure of the HLD-based HaloTag with its stabilizer, where the molecule has a tetrazole part located at the similar position (42). Analysis of the enzyme-inhibitor complex by ITC indicates the single binding site model with an n of 0.91 Ϯ 0.01, K d of 3.37 Ϯ 0.12 M, ⌬H of Ϫ5.24 Ϯ 0.12 kcal · mol Ϫ1 , and ⌬S of 8.14 Ϯ 0.12 cal · mol Ϫ1 ·°C Ϫ1 , where n is number of binding sites, K d is dissociation constant, ⌬H is a change in enthalpy, and ⌬S is a change in entropy (Fig.…”
Section: Figsupporting
confidence: 67%
“…This stabilization, reminiscent of the Shield system described above, allows for small molecule induced degradation and stabilization of the same system at once. [100] …”
Section: Inducers Of Protein Degradationmentioning
confidence: 99%
“…Immunoblotting revealed a geldanamycin-dependent increase in Hsp70 levels, consistent with the finding that Hsp90 inhibition leads to activation of Heat Shock Factor 1 (HSF1) and its target genes, including HSP70 [25] . Hsp70 and the associated E3 ubiquitin ligase CHIP play a key role in targeting intractably misfolded proteins to the UPS [26] , and we have shown that labeling HaloTag with hydrophobic tags leads to enhanced association with Hsp70 [27] . Together, this suggests that the Hsp70/CHIP complex mediates SARD-induced AR degradation and that elevated Hsp70 levels underlie the increase in SARD279 activity in the context of Hsp90 inhibition.…”
mentioning
confidence: 99%